Tweak it SG : a campaign to promote personal work-life effectiveness - Low, Sieu Ping (2014)
For years, the mandates for work-life flexibility were directed from top-down but Tweak It SG, a strategic communication campaign designed by three final-year students from Wee Kim Wee School of Communication and Information, aims to encourage working adults to step up by making small adjustments, or tweaks, to their everyday work and life. Targeted at Gen X and Gen Y working professionals, the campaign seeks to help working adults regain a sense of control in their day-to-day work-life flexibility by initiating small changes, or tweaks, to carve out time for their most important priorities. The campaign is executed in three key phases. Phase I aims to draw attention and generate interest through guerrilla publicity in the Central Business District (CBD), while Phase II aims to drive engagement through a sharing contest. The campaign concludes in Phase III with a compilation of contest submissions and expert insights to serve as inspiration for the wider community. This report includes the theoretical framework for campaign, preproduction research, detailed communication plans, tactics and its creative execution. Post-campaign survey, observational research, social media monitoring and metrics from both online and physical publicity efforts are proposed as part of campaign evaluation.